1998
DOI: 10.1007/s002689900349
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Dissemination during Laparoscopic Surgery: Tubes, Gas, and Cells

Abstract: Port-site metastasis has been an unexpected finding after laparoscopic surgery in gastrointestinal cancer patients. No clear explanation exists for this phenomenom. The aims of this study were to evaluate the dissemination pattern in an experimental model of hepatocarcinoma in the rat and summarize current knowledge about the risks and the results of experimental studies on cancer dissemination during laparoscopic surgery. NDA-induced hepatocarcinoma was obtained in Sprague-Dawley rats. Tumors were manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…This case shows that removal of unsuspected gallbladder carcinoma by the laparoscopic technique can produce one of these unusual complications: [3]. Similar proportions could be expected if cholecystectomies by these two different procedures were compared [2,4].…”
Section: Discussionsupporting
confidence: 65%
“…This case shows that removal of unsuspected gallbladder carcinoma by the laparoscopic technique can produce one of these unusual complications: [3]. Similar proportions could be expected if cholecystectomies by these two different procedures were compared [2,4].…”
Section: Discussionsupporting
confidence: 65%
“…Most metastases occurred in patients with advanced disease but an increasing number were found after operations for T1 and T2 gallbladder cancers as well as Duke’s A and B colorectal cancers. In this clinical situation numerous editorials and reviews have concluded that laparoscopic surgery for cancer should not be performed outside controlled studies until there are enough data about the clinical importance of this complication [82]. The preliminary data of the CAE port site registry (Workgroup Surgical Endoscopy) seem to comfirm such concerns.…”
Section: Discussionmentioning
confidence: 96%
“…The possible contribution of laparoscopic surgery to the dissemination of the tumor, although not proven, needs to be discussed. Metastases of an adrenocortical tumor occurring soon after laparoscopic surgery have rarely been reported up to now, but serious concern has recently been raised among surgeons regarding the suitability of laparoscopy for resection of malignant tumors [7, 8], even though laparoscopic surgery induces less trauma and immunosuppression than open surgery [9, 10]. Large tumors are usually not removed by laparoscopy because of their potential malignancy but the cut-off size is usually considered to be around 5 cm [11].…”
Section: Discussionmentioning
confidence: 99%